Evaluation of the Important Properties of Liquid Crystal Elastomers (LCEs) - Majeed, Dlzar M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Liquid Crystal Elastomers (LCEs) have been the object of growing interest in recent years due to the combination of mesogenic ordering and rubber elasticity which allows them to respond to thermal stimuli by changing their shape, size and optical properties. The use of LCEs thus makes it possible to convert small quantities of external energy to mechanical energy which makes it easy to be used as energy harvesting. This paper will firstly focus on thermal and mechanical properties of LCEs it will be seen that they will be affected by elasticity of the polymer backbone and the nature of mesogenic monomer. Following this, the focus will turn to the electric field, light, and thermal energy that can be converted into mechanical energy induces thermomechanical, electromechanical and electrooptical effects by such materials. It will be observed that the shape of LCE materials can be changed through changing orientation of LC. Additionally, swollen samples can minimize threshold field by a factor of 200 compared with unswollen samples. Then, the emphasis will go to the impact of mixing nanoparticles with the LCE samples on its behaviour. This is done by increasing crosslinking agent content of the sample and then its impact is shown by the strain-stress curve which leads to reduction in the degree of nematic phase and increase in Young’s modules. The paper then gives a future direction to expand the work for instance its application in photovoltaic systems to convert solar energy into electricity.
Keywords: liquid crystal elastomers rubber elasticity photovoltaic solar energy crosslinking